One hundred years of solitude eaudiobook - Márquez, Gabriel García (Blackstone Audio, Inc., and Buck 50 Productions, LLC, 2013)
Coming soon to Netflix as a highly anticipated series adaptation starring Claudio Cataño, Jerónimo Barón, and Marco González One of the twentieth century's enduring works, One Hundred Years of Solitude is a widely beloved and acclaimed novel known throughout the world and the ultimate achievement in a Nobel Prize–winning career. The novel tells the story of the rise and fall of the mythical town of Macondo through the history of the Buendía family. Rich and brilliant, it is a chronicle of life, death, and the tragicomedy of humankind. In the beautiful, ridiculous, and tawdry story of the Buendía family, one sees all of humanity, just as in the history, myths, growth, and decay of Macondo, one sees all of Latin America. Love and lust, war and revolution, riches and poverty, youth and senility, the variety of life, the endlessness of death, the search for peace and truth—these universal themes dominate the novel. Alternately reverential and comical, One Hundred Years of Solitude weaves the political, personal, and spiritual to bring a new consciousness to storytelling. Translated into dozens of languages, this stunning work is no less than an account of the history of the human race.